An Analysis of the Type of Questions Posed by Teachers in English-Medium Instruction at University Level - Aintzane Doiz; David Lasagabaster (MDPI AG, 2023)
Teacher-led questions not only guide meaning-making interactions but they also scaffold students' learning, and this is especially important in English-medium instruction (EMI). Due to the scant literature on this topic in higher education, this article analyses what type of questions EMI history lecturers pose and whether they are subject to individual differences. The study is based on 12 two-hour lectures whose transcriptions were analysed by three researchers. The results showed that instructional or content question types were much more commonplace than regulative questions (related to classroom procedures). Confirmation check, display and referential questions, which belong in the instructional category, were not posed to fulfil their intended pedagogic goals, a limitation accentuated by students' trend to provide short responses. These results reveal the need to design teacher training courses aimed at developing teachers' interactional abilities. Since questioning practices varied considerably between lecturers, customized training sessions should also be considered.